Constructivist Approaches in a Dual-Language Classroom. (2nd April 2016) - González-Carriedo, Ricardo; Bustos, Nancy; Ordóñez, Jorge
Abstract : Dual-language programs are becoming increasingly popular among educators and the public in general. In these programs, students aim at attaining full proficiency in English and another language while reaching an academic achievement at or above grade level. This article describes a series of pedagogical practices in the context of dual-language classrooms. We set the discussion across three defining characteristics of our constructivist perspective: learning as collaboration, teachers as facilitators, and language and culture as intertwined elements in schools. In sum, we postulate that dual-language programs bring equity to schools.